Kajian tentang Tingkat Ketidakhadiran Guru Sekolah Dasar dan Dampaknya terhadap Siswa - Philip Suprastowo (Jurnal Pendidikan dan Kebudayaan, 2013)
This study is a research result that aims to find out: 1) the level of absenteeism of elementary school teachers; 2) profile of teacher’s absenteeism level in terms of aspects of education background, employment status, and certificate ownership; 3) causes of absenteeism factor; 4) impact of teacher’s absenteeism on school and student learning performance; and 5) efforts that has been done in minimizing teacher’s absenteeism. The study was conducted through a survey in 20 regencies/cities as samples that determined by cluster random sampling according to region distribution and a consideration on population distribution of number of teachers in that region. There were 168 primary schools involved in this study which determined randomly. Results of this study found that: 1) level of absenteeism in primary school teachers was relatively lower, that was 6.6%; 2) profile of absenteeism teachers were dominant in teachers with high school education, Civil Servants Status, and have certified; 3) the main cause of absenteeism of teachers was due to be assigned by school and other interests, including the needs of teachers with official permission; 4) the impact of teacher absenteeism was disruption on learning process, students deviant behavior, decrease in student achievement and school image; and 5) school has tried to overcome the problems by setting up and assigning substitute teachers/picket teachers/part-time teachers, and education office in regencies/cities preventively overcome the absenteeism of teachers by applying disciplinary rules and sanctions for absenteeism teachers consequently and consistently.